2020
DOI: 10.1002/jee.20361
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between undergraduate student diversity and the representation of women of color faculty in engineering

Abstract: Background: Despite the critical role of faculty diversity in the persistence and academic experiences of undergraduate students as well as in the development of engineering innovations, women of color (WoC) faculty are still underrepresented in engineering programs across the United States. Purpose/Hypothesis: This study identifies whether the demographic composition of undergraduate engineering students is correlated with the representation of WoC faculty. It also highlights the institutional-and departmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 102 publications
1
47
0
Order By: Relevance
“…Consequently, the persistence of WoC faculty in engineering has important implications for the number of WoC students completing degrees in engineering and eventually pursuing faculty roles. Consistent with Main, Tan, et al (2020), our results highlight the lack of WoC PhDs in engineering fields, suggesting that to increase This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Consequently, the persistence of WoC faculty in engineering has important implications for the number of WoC students completing degrees in engineering and eventually pursuing faculty roles. Consistent with Main, Tan, et al (2020), our results highlight the lack of WoC PhDs in engineering fields, suggesting that to increase This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionsupporting
confidence: 84%
“…Yet, the participation of WoC in the engineering professoriate is critical to promoting diversity efforts because WoC are role models and mentors to WoC graduate and undergraduate students in engineering. Main, Tan, et al (2020), for example, demonstrated that the prevalence of WoC faculty is associated with the prevalence of WoC undergraduate students in engineering. Consequently, the persistence of WoC faculty in engineering has important implications for the number of WoC students completing degrees in engineering and eventually pursuing faculty roles.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified a wide range of factors that are associated with student major choice. In general, these factors can be organized into three main categories: individual characteristics and factors, social influences, and structural factors (e.g., Adelman, 1998;Blickenstaff, 2005;Cruz & Kellam, 2018;Darolia et al, 2020;Griffith & Main, 2021;Johnson & Sheppard, 2004;Lent et al, 2008;Main et al, 2015;Main, Darolia, et al, 2017;Main & Ost, 2011, 2014Main, Tan, et al, 2020;Main, Xu, et al, 2017;Marra et al, 2012;Matusovich et al, 2010;Ong et al, 2011;Seymour & Hewitt, 1997;Tan et al, 2021;Tonso, 1999Tonso, , 2006Tsui, 2010). Individual characteristics can include student demographic characteristics, academic achievement, motivation, and identity, whereas structural factors can include high school characteristics, high school geographical location, and the availability of math and science courses.…”
Section: Factors Influencing College Major Choicementioning
confidence: 99%
“…Subsequent work has examined the role of social influences such as peers, teachers, and family members as determinants of major choice (e.g., Carnasciali et al, 2013;Cruz & Kellam, 2018;Godwin et al, 2014;Griffith & Main, 2021;Main et al, 2018;Main, Tan, et al, 2020). Indeed, Godwin et al (2014) showed that students with family members, particularly siblings, who are engineers are more likely to choose engineering than those without.…”
Section: Factors Influencing College Major Choicementioning
confidence: 99%
“…While scholars have explored the culture and climate of engineering environments as hostile or unwelcoming for future WOC faculty (e.g., Robinson et al, 2016), less attention has been given to why WOC continue to seek faculty positions and why they remain in the academy. Many reports that focus on improving the number of women faculty in engineering do not specifically focus on women of color or intersectionality, missing out on crucial research that could assist with WOC recruitment and retention (e.g., Main et al, 2020). At the same time, there are few empirical studies that describe WOC faculty in STEM fields (cf., Ong et al, 2011Ong et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%